Effect of multi-component school-based program on body mass index, cardiovascular and diabetes risks in a multi-ethnic study - Paula Costa-Urrutia; Rafael Álvarez-Fariña; Carolina Abud; Valentina Franco-Trecu; Julián Esparza-Romero; Cruz Mónica López-Morales; Martha Eunice Rodríguez-Arellano; Jaime Valle Leal; Valentina Colistro; Julio Granados (BMC, 2019)
Abstract Background Mexico occupies one of the first places worldwide in childhood obesity. Its Mestizo and Indigenous communities present different levels of westernization which have triggered different epidemiological diseases. We assessed the effects of a multi-component school-based intervention program on obesity, cardiovascular and diabetes risk factors. Methods A physical activity, health education and parent involvement (PAHEPI) program was developed and applied in six urban (Mestizo ethnic group) and indigenous (Seri and Yaqui ethnic groups) primary schools for 12 weeks. A total of 320 children aged 4-12 years participated in intervention program; 203 under Treatment 1 (PAHEPI program) and 117, only from Mestizo groups, under Treatment 2 (PAHEPI+ school meals). For Body Mass Index (BMI), cardiovascular and diabetes factors, pairwise comparisons of values at baseline and after treatments were done using Wilcoxon signed rank test. Generalized linear models were applied to assess the intervention effect by age, sex and nutritional status in relation to ethnicity and treatment. Results We observed improvements on BMI in children with overweight-obesity and in triglycerides in the three ethnic groups. The Mestizo ethnic group showed the largest improvements under Treatment 2. While Seris showed improvements only in cardiovascular risk factors, Yaquis also showed improvements in diabetes risk factors, though not in BMI. Conclusions This study showed that the same intervention may have positive but different effects in different ethnic groups depending on their lifestyle and their emerging epidemiological disease. Including this type of intervention as part of the school curriculum would allow to adapt to ethnic group in order to contribute more efficiently to child welfare. Trial registration This study was retrospectively registered under the identifier NCT03768245.